Utilization-Focused Evaluation (Better Evaluation)
Utilization-Focused Evaluation (UFE), developed by Michael Quinn Patto n, is an approach based on the principle that an evaluation should be judged on its usefulness to its intended users. Therefore evaluations should be planned and conducted in ways that enhance the likely utiliz ation of both the findings and of the process itself to inform decisio ns and improve performance.